Youth Empowerment Workshop: Building Youth Capacity to Contribute to the Improvement of the Youth Development Index in South Kalimantan - Rakhmawati, Aneta; Rizkyka, Adetya Nor (Universitas Negeri Semarang, 2025)
According to Undang-Undang Nomor 40 tahun 2009 pasal 16, Youth who play an active role are a moral force, social control, and agents of change in all aspects of national development. However, many youths are unsure how to begin participating and playing active roles in society. They often doubt their ability to contribute, lack of education, information access, and resources frequently become the primary obstacle. To address these challenges and improve the Youth Development Index (YDI), as well as support the youth development strategies of the Ministry of Youth and Sports of the Republic of Indonesia (Kemenpora), Purna Caraka Muda Indonesia (PCMI) South Kalimantan and Gen Z Movement organized a seminar aimed at providing adequate education, training, and support. The program aimed to boost youths' confidence and motivation to engage in social projects. The seminar was attended by 200 youths, including members of various communities and university students in Banjarmasin. The implementation methods involved presentations from two keynote speakers, followed by an interactive discussion session. Subsequently, participants were divided into 10 groups to design social project plans and deliver presentations. Evaluation results indicated that 65% of participants were very satisfied, and 35% were satisfied with the seminar. Furthermore, over 90% of participants reported that the seminar helped them understand how to design effective social projects. This activity demonstrates the potential for structured seminars to empower youth and foster their active participation in society development